Overexpression of miR-223 Promotes Tolerogenic Properties of Dendritic Cells Involved in Heart Transplantation Tolerance by Targeting Irak1 - Yuan, Shun; Chen, Yuanyang; Zhang, Min; Wang, Zhiwei; Hu, Zhipeng; Ruan, Yongle; Ren, Zongli; Shi, Feng (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are key mediators of transplant rejection. Numerous factors have been identified that regulate transplant immunopathology by modulating the function of DCs. Among these, microRNAs (miRNAs), small non-coding RNA molecules, have received much attention. The miRNA miR-223 is very highly expressed and tightly regulated in hematopoietic cells. It plays an important role in modulating the immune response by regulating neutrophils and macrophages, and its dysregulation contributes to multiple types of immune diseases. However, the role of miR-223 in immune rejection is unclear. Here, we observed expression of miR-223 in patients and mice who had undergone heart transplantation and found that it increased in the serum of both, and also in DCs from the spleens of recipient mice, although it was unchanged in splenic T cells. We also found that miR-223 expression decreased in lipopolysaccharide-stimulated DCs. Increasing the level of miR-223 in DCs promoted polarization of DCs toward a tolerogenic phenotype, which indicates that miR-223 can attenuate activation and maturation of DCs. MiR-223 effectively induced regulatory T cells (Tregs) by inhibiting the function of antigen-presenting DCs. In addition, we identified Irak1 as a miR-223 target gene and an essential regulator of DC maturation. In mouse allogeneic heterotopic heart transplantation models, grafts survived longer and suffered less immune cell infiltration in mice with miR-223-overexpressing immature (im)DCs. In the miR-223-overexpressing imDC recipients, T cells from spleen differentiated into Tregs, and the level of IL-10 in heart grafts was markedly higher than that in the control group. In conclusion, miR-223 regulates the function of DCs via Irak1, differentiation of T cells into Tregs, and secretion of IL-10, thereby suppressing allogeneic heart graft rejection.